Co‐expression of opsins in the eye photoreceptor cells of the terrestrial slug Limax valentianus. Issue 18 (28th June 2019) - Matsuo, Ryota; Koyanagi, Mitsumasa; Nagata, Akane; Matsuo, Yuko
Abstract: Visual opsins coupled with Gq ‐type G protein have been considered to be responsible for the vision in mollusks. Recent transcriptomic studies, however, revealed the presence of opsin mRNA belonging to different groups of opsin subfamilies in the eyes of mollusks. In the present study, we found that at least three different opsins, Gq ‐coupled rhodopsin, opsin5A, and xenopsin, are co‐expressed in the rhabdomeric photoreceptor cell in the eyes of the terrestrial slug Limax valentianus . These opsins were all localized to the microvilli of the rhabdomere. Co‐expression of rhodopsin and opsin5A mRNA was also demonstrated by dual fluorescence in situ hybridization. Co‐expression of multiple opsins in the rhabdomeric photoreceptors cells may explain the previously reported shift in the action spectra of the electroretinogram of eyes of Limax flavus between the light‐ and dark‐adapted states, which was also reproduced in the present study in L. valentianus . Abstract : We found at least three different opsins, Gq ‐coupled rhodopsin, Opn5A, and xenopsin are all co‐localized to the rhabdomere of the eye photoreceptor cells of the terrestrial slug Limax valentianus . Co‐expression of multiple kinds of opsin species may explain the shift of the spectral tuning curves of ERG between the dark‐ and light‐adapted states.